2023
DOI: 10.1093/plphys/kiad033
|View full text |Cite
|
Sign up to set email alerts
|

microRNA408 and its encoded peptide regulate sulfur assimilation and arsenic stress response in Arabidopsis

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that play a central role in regulating various developmental and biological processes. The expression of miRNAs is differentially modulated in response to various biotic and abiotic stresses. Recent findings have shown that some pri-miRNAs encode small regulatory peptides known as microRNA-encoded peptides (miPEP). miPEPs regulate the growth and development of plants by modulating corresponding miRNA expression; however, the role of these peptides under different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Several reports have been published on the characterization of plant miPEPs; however, the molecular mechanism underlying miPEP action remains elusive. The application of exogenous miPEP to promoter-reporter lines has been shown to enhance reporter expression (Lauressegues et al, 2015, Sharma et al, 2020, Kumar et al, 2023, Lauressegues et al, 2022). Notably, recent evidence in animals indicates the regulation of miR-31 expression through its encoded peptide, miPEP31 (Zhou et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have been published on the characterization of plant miPEPs; however, the molecular mechanism underlying miPEP action remains elusive. The application of exogenous miPEP to promoter-reporter lines has been shown to enhance reporter expression (Lauressegues et al, 2015, Sharma et al, 2020, Kumar et al, 2023, Lauressegues et al, 2022). Notably, recent evidence in animals indicates the regulation of miR-31 expression through its encoded peptide, miPEP31 (Zhou et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…We further revealed that hsw instead of HSW was specifically integrated into cell control pathways via affecting KLUH in the transcription regulatory pathway, RGA in the G‐protein signaling pathway, and ARF2 in the auxin pathway (Li et al, 2019b), and that hsw might be also co‐involved into seed size and yield control with GmARPN , GmST05 , GmSWEET10a , and GA20OX . Particularly, GmARPN was a significant DEG in hsw ‐manipulated transgenic soybean compared with “Jack.” In A. thaliana , ARPN could be targeted by miR408 , thus forming the miR408 ‐ ARPN regulatory module to regulate seed yield and plant size (Dong et al, 2005; Pan et al, 2018; Song et al, 2018; Kumar et al, 2023). Moreover, miR408 primarily regulates cell expansion instead of cell proliferation (Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, GmARPN was a significant DEG in hsw-manipulated transgenic soybean compared with "Jack." In A. thaliana, ARPN could be targeted by miR408, thus forming the miR408-ARPN regulatory module to regulate seed yield and plant size (Dong et al, 2005;Pan et al, 2018;Song et al, 2018;Kumar et al, 2023). Moreover, miR408 primarily regulates cell expansion instead of cell proliferation (Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miPEP408 emerges as a crucial player in arsenic detoxification by modulating the sulfur reduction pathway. This insight into the regulatory role of miPEP408 adds to our understanding of plant responses to environmental stresses, paving the way for potential applications in crop improvement and stress management strategies (Cummins et al, 2011; Kumar et al, 2023; Kumar & Trivedi, 2018; Dixit et al, 2015a, 2015b, 2016).…”
Section: Heavy Metal Toxicitymentioning
confidence: 98%
“…Plant peptides are synthesized from precursor proteins or small open reading frames (sORFs) embedded within transcripts. These sORFs comprise 100 codons or less and lie either in the 5′‐leader sequence of a messenger RNA or are embedded within the primary transcripts of microRNAs (miRNAs) or are present within transcripts that code for short proteins of length <100 amino acids (Gautam et al, 2023; Hanada et al, 2013; Kumar et al, 2023; Lauressergues et al, 2015; Lauressergues et al, 2022; Ormancey et al, 2023; Sharma et al, 2020; Von Arnim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%